The Period of Production and Derived Concepts - Fleming, J. Marcus (Review of Economic Studies, 1935)
Journal Article The Period of Production and Derived Concepts Get access J. Marcus Fleming J. Marcus Fleming Edinburgh Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 1, October 1935, Pages 1–17, https://doi.org/10.2307/2967567 Published: 01 October 1935